Ginseng and health outcomes: an umbrella review - Li, Zhongyu; Wang, Yang; Xu, Qing; Ma, Jinxin; Li, Xuan; Tian, Yibing; Wen, Yandong; Chen, Ting (Frontiers in Pharmacology, 2023)
Background: Ginseng consumption has been associated with various health outcomes. However, there are no review articles summarizing these reports. Methods: PubMed, Embase, the Cochrane Library of Systematic Reviews, Scopus, CNKI and Wanfang databases were searched from inception to 31 July 2022. The Assessment of Multiple Systematic Reviews-2 (AMSTAR-2) and Grading of Recommendations Assessment, Development and Evaluation (GRADE) systems were used to assess the methodological quality and quality of evidence in each meta-analysis, and the results were summarized in a narrative form. Results: Nineteen meta-analyses that met the eligibility criteria were identified from among 1,233 papers. The overall methodological quality was relatively poor, with only five studies being low-quality, and 14 critically low-quality. When compared with control treatments (mainly placebo), ginseng was beneficial for improving fatigue and physical function, sexual function, menopausal symptoms, metabolic indicators, inflammatory markers, unstable angina and respiratory diseases. Adverse events included gastrointestinal symptoms and potential bleeding; however, no serious adverse events were reported. Conclusion: This umbrella review suggests that ginseng intake has beneficial therapeutic effects for diverse diseases. However, the methodological quality of studies needs to be improved considerably. In addition, it is imperative to establish the clinical efficacy of ginseng through high-quality randomized controlled trials.